Turkey and the Greater Eurasian Partnership: Opportunities and Challenges in \"Amalgamated\" Regionalism - ERŞEN, EMRE (My University, 2023)
The Greater Eurasian Partnership (GEP), introduced by Russia in 2015, is a regional integration project that aims to encompass the Eurasian Economic Union (EAEU), the Belt and Road Initiative (BRI), the Shanghai Cooperation Organization (SCO), and the Association of Southeast Asian Nations (ASEAN). With this broad spectrum, it embodies various forms of regionalism, arranges a flexible institutional structure for non-/governmental actors without denting their other regional affiliations and provides commercial, developmental, and security opportunities. Such features could also facilitate the GEP\"s ability to enhance Turkey\"s recent efforts to deepen its relations with Asia. In return, Turkey could play several key roles for the GEP with its \"dialogue partner\" status in the SCO, \"Middle Corridor\" initiative for the BRI, and well-established links in Central Asia. Originating from potential mutual interests, this study applies a theoretical perspective underlining the commonalities of various regionalism categories to analyze the GEP\"s amalgamated nature and highlight its significance for Turkey\"s political-economic priorities without undermining its traditional ties with the West.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Siyaset Bilimi; Uluslararası İlişkiler; Social Sciences and Humanities; Sociology; Political Science; International Relations; ULUSLARARASI İLİŞKİLER; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); INTERNATIONAL RELATIONS; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); Genel Sosyal Bilimler; Sosyal Bilimler ve Beşeri Bilimler; General Social Sciences; Social Sciences & Humanities; Russia; China; Shanghai Cooperation Organization; foreign policy; geopolitics